1976
DOI: 10.1172/jci108441
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of lymphocyte subpopulations in severe combined immunodeficiency. Evidence against a stem cell defect.

Abstract: A B S T R A C T Surface markers typical of T and B lymphocytes were present on varying proportions of peripheral blood lymphocytes from three infants with severe combined immunodeficiency disease. Despite this, functions mediated by T and B cells were either absent or very minimal in all three, including cell-mediated responses in vivo; the in vitro proliferative response to mitogens, allogeneic cells, or antigens; effector cell function in lymphocyte-antibody lymphocytolytic interaction assays; and in vitro s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Key among these is the recent appreciation that such disorders may not all be caused by an intrinsic inability of stem cells to fully differentiate into mature lymphoid cells (1)(2)(3)(4). In some forms of immunoglobulin deficiency, apparently mature bursa-equivalent (B) lymphocytes are present in normal numbers (2).…”
Section: Introductionmentioning
confidence: 99%
“…Key among these is the recent appreciation that such disorders may not all be caused by an intrinsic inability of stem cells to fully differentiate into mature lymphoid cells (1)(2)(3)(4). In some forms of immunoglobulin deficiency, apparently mature bursa-equivalent (B) lymphocytes are present in normal numbers (2).…”
Section: Introductionmentioning
confidence: 99%
“…The basis for this paradox is believed to be the abnormal differentiation of B and T cell precursors (22). Inadequate numbers of helper T cells have been implicated in a few patients (4,24) and several authors have also suggested a role for excessive numbers of suppressor T cells, which has been documented in at least one case (21). Certainly other forms of immunodeficiency, including subgroups of patients with common variable hypogammaglobulinemia selective IgA deficiency, and X-linked agammaglobulinemia; have been described with increased numbers or function of suppressor T lymphocytes (1,25,27).…”
Section: Discussionmentioning
confidence: 99%
“…1). Suppression was occasionally noted in cocultures containing cells from patients (19) in anotherassay system. However, the likelihood that suppressor cells can play a role in the immunodeficiency of SCID be- (26,27) and Gelfand et al (4,28), and such patients might be immunologically reconstituted by treatment with thymus transplantation alone.…”
Section: Methodsmentioning
confidence: 99%
“…Mononuclear cells were first isolated by floatation on metrizoate/Ficoll cushions and then further fractionated by velocity sedimentation at unit gravity (7). Cells from different fractions were pooled to yield the following cell populations: pool 1 (fractions [1][2][3][4][5][6][7][8][9][10], consisting largely ofcells ofthe myeloid series; pool 2a (fractions 11-13), consisting mainly of monocytes and a few large lymphocytes; pool 2b (fractions 14-16), containing predominantly medium sized lymphocytes; and pool 3 (fractions [17][18][19][20][21][22][23][24], containing mainly small lymphocytes.…”
Section: Methodsmentioning
confidence: 99%